Psychometric Evaluation of the Indonesian Version of the Character Scale in Adolescents - Devi Lusiria; Mario Pratama; Fidia Oktarisa; Puan Maharani (Journal of Educational, Health and Community Psychology, 2026)
Adolescent character development is increasingly important in the context of rapid technological and social change. However, psychometrically validated instruments for assessing adolescent character in Indonesia remain limited. This study aimed to adapt and evaluate the psychometric properties of the Indonesian version of the Character Scale, focusing on internal consistency, item discrimination, and construct validity. A total of 834 adolescents aged 11–19 years participated in the study. Data were collected using the adapted Character Scale and analyzed through item analysis, reliability testing, and confirmatory factor analysis (CFA). The results showed very high internal consistency (Cronbach’s α = .986), although this value may also indicate potential item redundancy. All items demonstrated acceptable item–rest correlations above .40. CFA supported the proposed eight-factor structure, with acceptable model fit indices (RMSEA = .062, CFI = .954, TLI = .949, NFI = .941), and all factor loadings were statistically significant. These findings provide initial evidence that the Indonesian version of the Character Scale is a psychometrically sound instrument for assessing adolescent character in research and educational contexts.